CONCEPTUAL STUDY ON THE MANAGEMENT OF FRESH WOUND: A REVIEW ARTICLE - Singh, Manmahendra; Singh, Shailendra; Hemanth, P; Sharma, Sanjeev (International Research Journal of Ayurveda & Yoga, 2024)
Wound healing is a normal biological process that occurs natu rally as long as the infection does not hinder it. Both freshly prepared incisional and excisional wound experimental models, several monoherbal and polyherbal formulations have been reported to hasten / accelerate wound healing process.Different herbal formulations have been reported to hasten/accelerate the process of wound healing by enhancing epitheliazation, neovascularization, formation of granulation tissue, collagen synthesis, wound contraction, tensile strength, etc. As these studies have been conducted in freshly prepared non-infected wounds, it is difficult to ascertain the wound healing potential of these formulations in absence of microbial colonization/infection and results are not